Persepsi Orang Tua Terhadap Dampak Negatif Permainan Online Roblox pada Siswa Sekolah Dasar - Rismawati, Devi; Mirnawati, Lilik Binti; Wahyuni, Holy Ichda (Education Journal : Journal Educational Research and Development, 2026)
This study aims to describe parents' perception of the adverse influence of the online game Roblox on elementary school students, focusing on four dimensions: social, academic, financial, and psychological. This study uses a qualitative approach with a phenomenological study. The data source consists of primary data, namely the parents of three elementary school students who are active Roblox users, and secondary data in the form of supporting documents. The data collection techniques used were semi-structured in-depth interviews, observations, and documentation. The instruments are in the form of interview guides and observation sheets. Data analysis is carried out including data reduction, data presentation, and conclusion drawing and verification. The results of the study showed that parents perceive the bad influence of Roblox as an interrelated syndrome. In the social aspect, Roblox is perceived to shift children's interactions to the virtual world and disrupt family communication. In the academic aspect, this platform is considered a major distraction from concentration and a trigger for procrastination. On the financial aspect, concerns include uncontrolled transactions and the internalization of consumptive value based on virtual social status. On the psychological aspect, parents observe emotional lability and early symptoms of dependence, where the child's emotional well-being becomes highly tied to the experience in the game. It was concluded that parents perceive Roblox not as just entertainment, but as a complex digital ecosystem that simultaneously has the potential to socially isolate children, disrupt academic achievement, distort financial understanding, and threaten their psychological stability.